ANALYSIS ON THE ACCEPTANCE OF EDMODO AS INSTRUCTIONAL TOOL USING TECHNOLOGY ACCEPTANCE MODEL (TAM) AMIDST COVID-19 PANDEMIC - Sepillo, Geoffrey S (Journal of Agriculture and Technology Management; Vol 23 No 2 (2020): Vol 23 No 2 (2020): Journal of Agriculture and Technology Management (JATM) Volume 23 July - December 2020 Issue, 2020)
The main purpose of this research study was to analyze the acceptance of Edmodo as an instructional tool using the Technology Acceptance Model (TAM) as to perceived usefulness, perceived ease of use, behavior intention, and actual use amidst COVID-19 pandemic. This research study utilized descriptive research design and quantitative analysis. Findings revealed that the faculty acceptance of the utilization of Edmodo as an instructional tool as to perceived usefulness, perceived ease of use, behavior intention, and actual use is acceptable.